Development and application of chlorine-free antifreeze and dust suppression agent for transportation pavement of surface coal mines in Alpine areas - Xiaoliang Zhao; Shaohui Feng; Fangwei Han; Bandna Bharti; Zhao Lian; Zhaolin Shen; Jing Du; Yide Li; Qi Shi (PLoS ONE, 2025)
Truck transportation pathways in surface coal mining operations are significant sources of dust emissions. Currently, water sprinkling and aqueous dust suppressants are commonly used on haul roads in surface coal mines. However, in the alpine regions of northern China, this practice poses serious safety risks due to road surface freezing. Addressing the conflict between effective dust suppression and the risk of icing on haul roads presents a significant practical challenge. To overcome this issue, a chlorine-free antifreeze dust suppressant was developed through a systematic process involving dust characterization, monomer screening, orthogonal formulation design, performance testing, and field validation. The investigation identified sodium dodecylbenzene sulfonate, glycerol, polyacrylamide complexed with ethylene glycol, potassium acetate, and potassium formate as the optimal monomer materials. The dust suppressant shows minimal corrosiveness, resistance to wind erosion and evaporation, and has a freezing point of – 35.3°C, representing a substantial improvement over traditional water and aqueous dust suppression methods. Field testing demonstrated that the formulated chlorine-free antifreeze dust suppressant extended effective dust suppression duration to 8 days. Moreover, the economic costs associated with its application were deemed low. These findings emphasized the efficacy and practical utility of the chlorine-free antifreeze dust suppressant for mitigating dust emissions along transportation routes within alpine open pit coal mines.